(untitled) (Experimental biology, 2015)
Use of carbonize sorbents (CRS-1) as the carrier of lactobacilli provides address delivery of a probiotic preparation and an attachment to mucous intestines with the subsequent detoxication of a gastroenteric path and normalization of its microecology.